PENGARUH GRADE MATA KULIAH AKUNTANSI KEUANGAN YANG DIPEROLEH MAHASISWA AKUNTANSI TERHADAP KOMPETENSI PENYUSUNAN LAPORAN KEUANGAN (Studi Empiris pada Mahasiswa Jurusan Akuntansi, Fakultas Ekonomi UNTAN yang sedang menempuh perkuliahan Akuntansi Keuangan La - B41108146, Novra Maulana (Jurnal KIAFE, 2015)
Economic Faculty of Tanjungpura, especially Accounting Major is a medium that creates the First Bachelor Degree with the knowledge on Accounting. As the medium that being the base on subject focuses on Accounting, spesifically financial reporting, the scholars always meets the subjects related with financial reporting. To measure the result and competence of studying of the subject engaged by the scholars, the exam takes place, which being the base to measure the competence of the scholar related to the subject. This research intended to know how much the Grade owned by the scholars represents the competence in financial reporting that created with the knowledge in accounting process (financial Reporting) and Conceptual Framework for financial reporting. Population chosen in this research is the accounting scholar, that engaged in Advanced Financial Accounting 2 2013/2014. Limitation made on the sample, focused on 124 sample on Reguler A Accounting scholar on base research assumption that they had and already finished the Principles Accounting 1, Principles Accounting 2, Intermediate Accounting 1 and Intermediate Accounting 2 that being the subject that leads scholars to financial reporting and knowledge in Conceptual Framework for financial reporting. Result of the research show that the grade affect but not significant towards the competence in financial reporting. While F-Test show that grade affect only 11% on Competence in Financial Reporting and as 89% is the other variable that didn"™t included in this research. Keywords: Competence in financial reporting, knowledge in Conceptual Framework for financial reporting and Accounting Scholar.